2008
DOI: 10.1088/1367-2630/10/7/075019
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of non-uniformly seeded warm clouds in idealized turbulent conditions

Abstract: Abstract. We present a mean-field model of cloud evolution that describes droplet growth due to condensation and collisions and droplet loss due to fallout. The model accounts for the effects of cloud turbulence both in a large-scale turbulent mixing and in a microphysical enhancement of condensation and collisions. The model allows for an effective numerical simulation by a scheme that is conservative in water mass and keeps accurate count of the number of droplets. We first study the homogeneous situation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…In figures 6 and 7 we plot c g data from our simulations and compare with theoretical estimations. Overall, our results without gravity are consistent with theoretical predictions derived in [28,31,37] and other independent numerical studies reported in [22,29,33]. Several important observations can be made.…”
Section: Scaling Exponentsupporting
confidence: 92%
See 2 more Smart Citations
“…In figures 6 and 7 we plot c g data from our simulations and compare with theoretical estimations. Overall, our results without gravity are consistent with theoretical predictions derived in [28,31,37] and other independent numerical studies reported in [22,29,33]. Several important observations can be made.…”
Section: Scaling Exponentsupporting
confidence: 92%
“…For the cases without gravity, c g reaches a maximum value at St ∼ 0.6 and then decreases with the Stokes number. The empirical formula of Derevyanko et al [37] appears to overestimate c g for intermediate Stokes numbers, and underestimates c g for large Stokes numbers.…”
Section: Scaling Exponentmentioning
confidence: 86%
See 1 more Smart Citation
“…They observed that the clustering effect, and consequently the collision kernel, decreases as R λ increases for R λ > 100 and St = 0.4, while no significant Reynolds-number dependence was observed for St = 0.1. This is a relevant and significant observation, since many authors ignore this Reynolds-number dependence and assume a constant collision kernel irrespective of R λ (Saffman & Turner 1956;Derevyanko, Falkovich & Turitsyn 2008;Zaichik & Alipchenkov 2009) or assume a convergence to a constant collision kernel with increasing R λ (Ayala, Rosa & Wang 2008). A similar Reynolds-number dependence for St < 1 has now been confirmed by Rosa et al (2013).…”
Section: Introductionmentioning
confidence: 62%
“…how they depend on the Taylor-scale Reynolds number Re λ of the flow (see e.g. Derevyanko, Falkovich & Turitsyn 2008;Xue, Wang & Grabowski 2008). We consider suspensions of small, heavy and dilute particles, neglecting gravity.…”
Section: Introductionmentioning
confidence: 99%